Mental Healthcare in Prison: A Right or a Discretion? - Ryan, Lance (Auckland University of Technology, 2023)
Mental health care within prisons has been deemed a categorical failure. The increasing number of self-harm incidents and the growing prevalence of untreated mental illness among prisoners raise concerns about the efficacy of the current system. This research explores the cracks in the mental healthcare system across Aotearoa prisons, attributing the issues to the responsibility of the Department of Corrections, the conflation of treatment and rehabilitation, and a shortsighted focus on a reasonably equivalent healthcare standard that fails to meet legal requirements and public health needs. This paper aims to present a less-explored perspective on mental health care within prisons by advocating for a shift from the pursuit of equivalent standards to the attainment of equitable health outcomes. It argues that to fully comply with legislation in Aotearoa, mental healthcare in prisons should go beyond reaching parity with community standards and, instead, strive for outcomes comparable to those achievable in the community. The research critically examines the concept of reasonable equivalence of health care. It reviews existing scholarship that surveys the scope of the problem and analyses new treatment developments. However, this paper goes further by proposing a reframing of the approach to mental healthcare in prisons. The findings suggest that achieving equivalent health outcomes for prisoners requires a comprehensive overhaul of the mental healthcare system. This would involve enhancing individual capacity, improving general accessibility, coordinating stakeholders, and allocating additional resources beyond the current standards available in the community. The paper concludes by highlighting the need for strategic and systemic change in order to address prevailing issues, uphold legislative requirements, and meet the wider public health needs. This research contributes to the ongoing discourse on improving mental healthcare for prisoners and offers a fresh perspective that can inform future policy in practise.